Aspectos fundamentais da teologia do laicato a partir da exortação apostólica Christifideles Laici - Francisco, Fernando Rodrigues (2012)
This study aims to point out the fundamental elements of the theology of the laity present in the documents of the Magisterium of the Church, in a special way in the apostolic exhortation Christifideles Laici, from the blessed John Paul II. It is known that many of these elements had already been listed by renowned theologians way before the Second Vatican Council. However, it was with the Vatican II that the theology of the laity was consolidated and the laymen began to demand a greater participation in the organization and mission in the Church. In the first chapter we see that this council has established important concepts for understanding the theology of the laity: as 'people of God', 'participation', 'communion', 'common priesthood'. Through baptism all believers are co-responsible in the Church's evangelizing mission. Through this baptism all the faithful are co-responsable in the threefold mission of the church. By this sacrament the laymen faithful become participants of the triple munus of Christ. It is from this participation that spring the fundamental elements that characterize the theology of the laity: leadership, holiness, secular mission, ministries, offices, roles, charisms. The laymen faithful, in communion with the Church, working in the temporal reality and take the Good News of Jesus. In the second chapter we point out the essential elements of the theology of the laity present at apostolic exhortation Christifideles Laici. This post-synodal exhortation stated that the saving mission of the Church is held in the world by all baptized christians. The fundamental new of this exhortation is the act of the laymen in the Church and in the world. The lay aggregation and ecclesial criteria for these forms of associations constitute the heart of Christifideles Laici. In the third chapter we understand that the elements of the theology of the laity, well founded, would be useful not only to substantiate the sacrament of baptism and to solve the pastoral problems of the parishes, but also they would help to clarify the relationship between clergy and laymen, the various ministries and charisms, the various vocations and the sanctification of the laymen in the Church and the world. Finally, we saw the effort that the Church must still be taken in applying the theology of the laity, to be a more effective tool used in the dissemination of Gospel in the world. Much remains to be done for the recognition of the lay ministries and the work together with ordained ministers, however, Christifideles Laici pointed the baptism as a starting for a common mission, since all are members of one body whose head is Christ, into the New Evangelization